The LASER database: Formalizing design rules for metabolic engineering - Winkler, James D.; Halweg-Edwards, Andrea L.; Gill, Ryan T. (Metabolic engineering communications, 2015)
The ability of metabolic engineers to conceptualize, implement, and evaluate strain designs has dramatically increased in the last decade. Unlike other engineering fields, no centralized, open-access, and easily searched repository exists for cataloging these designs and the lessons learned from their construction and evaluation. To address this issue, we have developed a repository for metabolic engineering strain designs, known as LASER (Learning Assisted Strain EngineeRing, laser.colorado.edu) and a formal standard for disseminating designs to metabolic engineers. Curation of every available genetically-defined E. coli and S. cerevisiae strain from 310 metabolic engineering papers published over the last 21 years yields a total of 417 designs containing a total of 2661 genetic modifications. This collection has been deposited in LASER and represents the known bibliome of genetically defined and tested metabolic engineering designs in the academic literature. Properties of LASER designs and the analysis pipeline are examined to provide insight into LASER capabilities. Several future research directions utilizing LASER capabilities are discussed to highlight the potential of the LASER database for metabolic engineering. •We present the first developed repository for metabolic engineering designs.•A formalized standard is developed for curating and depositing designs.•A total of 279 E. coli and 138 S. cerevisiae designs are already stored.•Computational tools for analyzing the LASER database are presented.•Potential applications for formalizing design rules are explored.